Comparison Of Dental Caries Experience Among 35-40 Year Old Population Using Dmft And Dmfs Index - An Institution Based Cross Sectional Study - A, SUBASHRI.; K, SOWMYA.; GANAPATHY, DHANRAJ (The journal of contemporary issues in business and government, 2021)
In recent years, there is much higher prevalence and severity of dental caries. Even the countries which had low incidence of dental caries have been experiencing an increase in the prevalence of caries. Patterns of dental caries distribution have also been changed over the years with a small group of people representing the high-risk minority. Therefore a more detailed epidemiological study on prevalence of dental caries is required. The aim of the current study was to assess the prevalence and compare dental caries of 35 to 40 year old population visiting a private dental college using DMFT and DMFS indexes. A total of 954 who visited Saveetha dental college from the period of June 2019 to March 2020 were included in the study. Demographic details were collected. The caries experience of the 35 to 40 year old population was evaluated using the DMFT and DMFS indexes. Data was analysed using IBM SPSS Software Version 20.0. Independent t test was used to compare the mean DMFT and DMFS score with age and gender respectively. The results revealed that the mean DMFT score in females (7.99±0.19) was more than males (6.47±0.16) and this was highly significant (p value- 0.00). Mean DMFS score was also higher in females (24.11± 0.74) than males and this was also highly significant (p value-0.00). Females were found to be more prone to dental caries with high prevalence found among the 38-40 years age group with respect to both DMFT and DMFS scores. More awareness must be created among the population about the incidence of caries and early restorative procedures to prevent further loss.